Mexico : Arrangement Under the Flexible Credit Line; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses the arrangement under the Flexible Credit Line (FCL) for Mexico. Mexico has achieved a high level of credibility in the institutional framework supporting macroeconomic policy formulation, and has a sustained a track record of implementing strong policies. Liquidity pressures have emerged in some market segments, while credit quality is also under strain in the consumer banking portfolio. The arrangement for Mexico is the first commitment under the IMF's FCL, and is particularly useful for crisis prevention as it provides the flexibility to draw on the credit line at any time.